A ten year review of depot medroxyprogesterone acetate contraceptive use at Rivers State University Teaching Hospital, South Nigeria - Nonye-Enyidah, Esther I.; Kasso, Terhemen (International Journal of Advances in Medicine, 2020)
Background: Depo Medroxyprogesterone Acetate (DMPA) also known as Depo provera is a long acting progestogen-only contraceptive injection used by women worldwide. It is given deep intramuscularly at interval of 3 months. It is easy to use, effective, safe, convenient and reversible. Objective was to determine the prevalence of DMPA contraceptive method and profile of its acceptors at the RSUTH. Methods: This was a retrospective study of 271 clients attending family planning clinic at the RSUTH from 1st January, 2008 - 31st December, 2017. Their records were retrieved from the clinic and reviewed. Data was extracted, coded and analyzed using the statistical package for social sciences (SPSS) IBM version 25.0 (Armonk, NY). Results: The prevalence rate of DMPA contraceptive among contraceptive acceptors at the RSUTH within the study period was 14.3 %. The modal age group was 30-34 years accounting for 103 (38.0%). Age range was 20-51 years. Two hundred and sixty eight (98.9%) had formal education. Majority of the clients had secondary level of education 209 (77.1 %). Of the 271 acceptors of DMPA, 175 (64.6%) were multipara. Most of the clients were married 259 (95.6%) and of Christian religion 265 (97.8%). Clinical personnel were the commonest source of information, accounting for 228 (84.1%). Conclusions: The prevalence of DMPA use over the study period was low. There is need for more counseling and enlightenment campaign to encourage our women to use this effective and safe method of contraception.